Synthesis of Schiff Base from 2,2´-Diaminodibenzyl with 2-Hydroxy Naphthaldehyde and its Complexes with Mn(II),VO(II) and UO2(II) - A. FILMWALA , ZOEB; M. Nandavadekar, Sanjay; M. PATIL, RAJU (Asian Journal of Chemistry, 2010)
The Schiff base has been prepared by the condensation of 2,2'-diaminodibenzyl with 2-hydroxy naphthaldehyde. The Schiff bases characterized by elemental analysis and spectral methods. The metal complexes of Mn(II), VO(II) and UO2(II) have been prepared by the reaction of Schiff base and characterization supported by spectral studies. The analytical and spectral data revealed the octahedral structure for Mn(II) and UO2(II) complexes and square pyramidal for VO(II) complex.